Penguatan Kemampuan Literasi Numerasi Melalui Program Kampus Mengajar Angkatan 3 di SD N 28 Parlondut - Sinaga, Yolanda; Sianipar, Maria Olivia Christina; Naibaho, Tutiarny; Prabawa, Ade Bagus Tegar (Sevanam: Jurnal Pengabdian Masyarakat, 2023)
Education is very important for the progress of a nation. With education, a nation can produce quality human resources capable of improving the nation's future. Education must be made a priority along with the rapid progress of the times and technology in order to be able to compete internationally. The world of education has had a big impact during the Covid-19 pandemic. The teaching and learning process in schools affected by the pandemic cannot be carried out optimally due to limited access and interaction between educators and students. This prompted the Ministry of Education and Culture to initiate Kampus Mengajar Program which provides opportunities for students to assist teachers and principals at the elementary and junior high school levels in the 3T (Lagged, Outermost, and Frontier) areas in carrying out learning activities. One of the schools targeted by this program is SD N 28 Parlondut which is located in Parlondut Village, Pangururan District, Samosir Regency, North Sumatra. The program is carried out for one semester by focusing on strengthening numeracy and literacy in the target school. Students will observe existing problems and will coordinate with educators in target schools to design ideas and improvements that need to be made. This program helps schools, teachers, and students in developing insight, skills and growing motivation to participate in the development of Indonesian education.